Shallow graves: a memoir of the Ethiopia-Eritrea war - Reid, Richard J. (Hurst & Company, 2020)
"This is a personal account of the war between Eritrea and Ethiopia, fought between May 1998 and June 2000, as well as of the periods immediately preceding and following the conflict. Shallow Graves traces shifting local perceptions of time, the nation and the region, beginning in the mid-1990s and concluding with the peace agreement signed between the two governments in 2018." From publisher's website